Pengenalan, Optimalisasi Optimalisasi Pengenalan Produk Unggulan Desa Melalui Pelatihan Website Promosi Kecamatan Patuk Gunungkidul - Astika Ayuningtyas; Yuliani Indrianingsih; Uyuunul Mauidzoh (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The development of information and computerized tenology has led to what is called the Internet and the World Wide Web (WWW). In addition, the dramatic development of the Internet has given users more choice and control over content, and also provides individuals, businesses, and public and private organizations with the opportunity to generate and disseminate information. The interactive features of the web can be an effective way to build and maintain mutually beneficial relationships if the web is used properly. The presence of the Internet has proven to have a positive impact on the development of a village, sub-district or district to introduce and inform the potential of its region. This is evident in several regions of Indonesia which have successfully used Internet facilities to introduce tourist destinations to the world. Therefore, the training on the promotion website is an effort to optimize the introduction of high quality village products in the district of Patuk and is also intended to follow the results of research on the design of a promotion of superior products and tourist objects on the web in Patuk Gunungkidul district. On the basis of the website promotion feasibility test during the training for each representative in 11 villages in the Patuk sub-district, 87.36% was obtained, so that it can be said that the Introduction of superior village products via promotional materials based on the website was optimal and met the needs of users.